An improved phenomenological model of vibrations for planetary gearboxes. (31st March 2021) - Zhang, Mian; Li, Decai; Zuo, Ming J.; Liu, Jun; Xiang, Hongbiao; Song, Yang; Wang, Kesheng
Abstract: Interpreting and understanding vibration characteristics are the cornerstone for health condition monitoring schemes of a planetary gearbox. Phenomenological modeling provides a concise and efficient mathematical description of sensor-related vibration measurements, thus allowing prior guidance for spectrum analysis to be relied on. In this paper, some overlooked problems during the modeling process in previous researches are pointed out and analyzed. Some discoveries are consequently obtained: First, the asymmetry of spectrum structure should be attributed to the magnitude randomness of gear meshing vibration rather than different phase angles of multiple-planet gears; Second, the basic frequency component to constitute a model, namely a product of the rotational frequency of a planet carrier and the number of planet gears, is far from sufficient to describe the actual vibrations; Finally, improper function the phases of multiple-planet gears will lose some sidebands that should have been. For these reasons, we map the phase variation of multiple-planet gears into the time-varying propagating distance, therefore, solving the neutralization phenomena of the frequency components. With consideration of the attenuation effect and random gear meshing magnitudes, an improved model is proposed to provide a more reasonable representation of the vibration behaviors, both for the dominant frequency components and structure. Simulation and experimental studies both demonstrate the higher fidelity and descriptive capability than the traditional models.